The Mechanical Properties of Laminated Bamboo with Different Types of Adhesive and Compression Pressures - Darwis, Zulmahdi; Basuki, Achmad; Bhayusukma, Muhammad Yani; Kristiawan, Stefanus Adi; Diharjo, Kuncoro; Wibowo, Cahyo Hadi; Saputro, Fathony Nada; Majid, Faishal Machfudz (Engineering, Technology & Applied Science Research, 2026)
Laminated bamboo, having a high strength -to-weight ratio, is getting popular for structural applications. This study evaluates how adhesive type (epoxy, polyurethane, and polyvinyl acetate) and compression pressure affect the mechanical properties and failure morphology of laminated bamboo (Dendrocalamus asper). The laminates were fabricated using the Multi Double Glue Layer (MDGL) method with cold pressing for 24 h. Tensile and shear tests were conducted in accordance with ASTM D143 to characterize mechanical behavior. Fracture surfaces were examined by macrophotography to classify failure modes. The results indicate that the epoxy adhesive provides the greatest tensile and shear strength, with failure occurring within the bamboo substrate, indicating an effective adhesive bond. Polyurethane (PUR) exhibited multiple failure modes coupled with intermediate mechanical performance, while Polyvinyl Acetate (PVAc) showed adhesive failure and offered the lowest strength. The optimum compression pressure was found to be 3.5 MPa, which allowed for effective adhesive infiltration between bamboo pores without causing excessive extrusion. Exceeding the pressure limit resulted in strength reduction due to the formation of voids, adhesive thinning, and microcracking of the substrate. Epoxy exhibited the highest Young’s modulus, due to its rigid and highly cross-linked molecular structure.